A workflow for rapid assessment of complex courtyard wind environment based on parallel lattice Boltzmann method. (1st April 2023) - Wu, Renzhi; Fang, Xiaoshan; Liu, Shuang; Li, Qiong; Brown, Robert; Yan, Junru
Abstract: A fast courtyard wind simulation platform based on the parallel courtyard Lattice Boltzmann Method (CLBM) is proposed to achieve comprehensive optimization of courtyard design structure and wind environment performance. The simulation workflow of CLBM is designed and implemented, and its accuracy is validated using two benchmark cases and Qinghui Garden in central Guangdong. The results show that CLBM achieves simulation accuracy on par with other simulations, with R 2 values greater than 0.8 and Root Mean Squared Error ( RMSE ) values less than 0.3 m/s for the building array case and RMSE values less than 0.2 m/s for the row of trees case. In the testbed courtyard, the Normalized Root Mean Squared Error ( NRMSE ) values range from 0.18 to 0.30, close to Ansys Fluent's NRMSE values of 0.07–0.33, and comparable to most peer studies with NRMSE values below 0.5. CLBM is also faster than traditional Computational Fluid Dynamics (CFD) models, with a workflow that is 19 times faster than Ansys Fluent and can produce wind environment simulation feedback in about 10 min. This model's speed and accuracy advantages make it well-suited for quickly simulating courtyard wind environments, even in the presence of complex combinations and rich vegetation. Architects can use this technique to regularly experiment with courtyard design elements and achieve evidence-based design of courtyard ventilation to fully realize the aesthetic appeal and maximize ventilation efficiency. Highlights: A parallelized Lattice Boltzmann Method simulates courtyard wind field. Benchmark validation and in-situ observations shows model efficiency and accuracy. Canopy drag force modeling enhances wind field simulation around vegetation. Optimized workflow facilitates evidence-based design of courtyard wind environments.